The Global Contradiction of The 21rst Century - Lane, Jan Eric (Advances in Social Sciences Research Journal, 2014)
Economic growth and environmental sustainability has been much debated: Can they be combined to give both prosperity and environmental protection? On the micro level, many projects show that this is indeed possible. But on the macro level, global emissions of greenhouse gases follow the advancement of country affluence closely. The link is the constantly increasing need for more energy, provided by fossil fuels.